TESTS FOR UZBEK LANGUAGE STUDENTS - Yarkulova Fotima Usmanovna; Norjigitova Ismigul ,Makhamatmusayeva Zilola,Saidullaeva Sevinch (Galaxy International Interdisciplinary Research Journal, 2023)
Testing is a great opportunity for students to raise their level of preparation in all subjects and update their knowledge of specialization in order to know the knowledge of students. The relevance of the choice of topic lies in the fact that the student can repeat the topics that have passed. We regularly update the modern educational process without a test control system, which has been increasingly used in the educational process over the past few years. The result of work in this direction was the creation of a state system of direction was the creation of a state system of testing in a number of subjects of the school cycle.